A BPMN extension to support discrete-event simulation for healthcare applications: an explicit representation of queues, attributes and data-driven decision points. Issue 5 (4th May 2018) - Onggo, B. S. S.; Proudlove, N. C.; D'Ambrogio, S. A.; Calabrese, A.; Bisogno, Stefania; Levialdi Ghiron, N.
Abstract: Stakeholder engagement in simulation projects is important, especially in healthcare where there is a plurality of stakeholder opinions, objectives and power. One promising approach for increasing engagement is facilitated modelling. Currently, the complexity of producing a simulation model means that the "model coding" stage is performed without the involvement of stakeholders, interrupting the possibility of a fully facilitated project. Early work demonstrated that with currently available software tools we can represent a simple healthcare process using Business Process Model and Notation (BPMN) and generate a simulation model automatically. However, for more complex processes, BPMN currently has a number of limitations, namely the ability to represent queues and data-driven decision points. To address these limitations, we propose a conceptual design for an extension to BPMN (BPMN4SIM) using model-driven architecture. Application to an elderly emergency care pathway in a UK hospital shows that BPMN4SIM is able to represent a more complex business process.